Clinical improvement, toxicity and future prospects of β-sitosterol: a review - Azka Khan Durrani; Momina Khalid; Awais Raza; Izza Faiz ul Rasool; Waseem Khalid; Muhammad Nadeem Akhtar; Ammar Ahmad Khan; Zunair Abdullah; Babirye Khadijah (CyTA - Journal of Food)
β-sitosterol is waxy substance, white in color distributed in a variety of natural plant sources cereals, pulses, legumes, vegetables, fruits, and herbs. Several clinical and preclinical investigations indicate that β-sitosterol has a wide range of important health advantages. It prevents many types of malignancies, lowers levels of low density lipoprotein (LDL), lowers the risk of coronary artery disease, heart attacks, and atherosclerosis, and supports the body’s natural healing process. It is found to have cancer-protective properties and has the potency to be beneficial against breast, prostate, colon, lung, stomach, and leukemia. The present review provides a complete analysis and examines the literature on β-sitosterol from different dietary sources, with a focus on its toxicological characteristics and nutraceutical qualities. It lays down the theoretical basis and justification for directing the future planning and execution of clinical studies intended to confirm the importance and possible toxicity of β-sitosterol.